Transformasi Kurikulum Ilmu Pengetahuan Sosial (IPS) di Indonesia: Sejarah, Pengaruh Global, dan Adaptasi Lokal - Qoidul Khoir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This writing aims to describe the development of the Social Studies curriculum in Indonesia. Social studies education in Indonesia did not just appear and develop, but through a long journey full of dynamics. This article reviews social studies education from a historical perspective and its development using historical research methods, which include the steps of heuristics, source criticism (external and internal), interpretation, and historiography. The development of the social studies curriculum in Indonesia has adopted the concepts of social studies education in several major countries, such as the United States and the United Kingdom, which became a reference because of the similarity of the conditions of multicultural society and the background of the country's unstable situation at that time. Nevertheless, the development of social studies education in Indonesia is adapted to the conditions of society and government in the country, which has an impact on the preparation of curriculum and implementation of learning in schools. Along with technological advances, social studies education also continues to grow by utilizing a variety of learning resources and media. In addition, the development of social studies learning materials also involves the active participation of the wider community.